A comparative study on the efficacy of antiemetic drugs to prevent per-operative nausea and vomiting among parturients undergoing caesarean section Under spinal anesthesia - Das, Pradip Chandra; Hossain, Mosharraf; Das, Tapas Kumar; Goswami, Mritunjoy; Muhib, Muhibullah; Ahasan, Muhammad Nazmul; Haque, Anwarul (Journal of Dhaka National Medical College & Hospital, 2025)
Background: Nausea and vomiting are undesirable per-operative events among parturients during cesarean section under spinal anesthesia. Therefore prophylaxis is recommended. Objectives: To compare & assess the effect of intravenous Ondansetron, Metoclopramide and Prochlorperazine Maleate administered before achieving spinal anesthesia for preventing per-operative nausea and vomiting. Materials and methods: This comparative study was done in the Department of Anesthesiology in Dhaka National Medical Institute Hospital, Dhaka from February 2024 to January 2025. Total 60 women, age ranged from 18-45 years undergoing caesarean section of both emergency and elective were included. They were divided into 3 groups as group A, B, C; each group comprising with 20 subjects. Group-A received intravenous metoclopramide, group-B received intravenous prochlorperazine maleate & group-C received intravenous ondansertron. Results: Among 20 patients of Group A, mean age was 26.53±5.9 years, height was 151.27±3.8cm and weight was 63.77±9.5kg; while in group B, mean age was 27.00±6.2 years, height was 152.10±4.7cm and weight was 62.97±9.1kg and for group C, mean age was 28.71±7.72 years, height was 153.24±5.2 cm and weight was 64.78±9.6kg. In group A (Metoclopramide), 6 patients (30.0%) had IONV and in group B (Prochlorperazine), 3 patients (15.0%) and in group C (Ondansetron), 1patient (5.0%) had IONV respectively. Regarding hypotension with IONV 5 patients (55.5%) in group A, 2 patients (25.0%) in group B and 1 patient (10.0%) in group C respectively. But statistically the difference was not significant. Conclusions: This study reveals that intravenous Ondansetron had superior effect in preventing nausea and vomiting among parturients undergoing caesarean section under spinal anesthesia in contrast to intravenous Metoclopramide and Prochlorperazine Maleate. J. Dhaka National Med. Coll. Hos. 2025; 31 (01): 29-32